Labelled as ‘risky’ in an era of control: how young people experience and respond to the stigma of criminalised identities - Deakin, Jo (European journal of criminology, 2020)
The construction and labelling of groups of young people as ‘risky’ triggers a multifaceted and dynamic social process of stigma that frequently results in reduced life chances and limited opportunities for self-development. Drawing on case-study data from four European countries, this article focuses on the ways in which stigma is reproduced through interactions and interventions that label young people. Our analysis explores how young people experience and understand stigma, and how they respond to it. Framed within a theoretical understanding of stigma as a form of power, we examine its components and cyclical process, its role in shaping policies of social control, and its consequences for groups of ‘risky’ young people. Our analysis builds upon and develops Link and Phelan’s (2001) reconceptualization of stigma to include reference to young people’s reactions and responses: alienation and marginalization; anger and resistance; empathy and generativity. We argue that stigma acts primarily as an inhibitor of young people’s engagement in wider society, serving to further reduce access to beneficial opportunities. However, some young people are able to resist the label, and, for them, resistance can become generative and enabling.info:eu-repo/semantics/publishedVersio